1993
DOI: 10.1111/j.1365-2621.1993.tb09387.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Edible Films: Modified Procedure for Water Vapor Permeability and Explanation of Thickness Effects

Abstract: The ASTM E96 Standard Method for determining water vapor permeability (WVP) was modified for hydrophilic edible films. Accurate measurement of relative humidity conditions and maintenance of 152 m/min air speeds were essential outside the test cups. The WVP Correction Method was developed to account for the water vapor partial pressure gradient in stagnant air layer of the test cup. Errors were as high as 35% without this correction. Applying these guidelines explained commonly observed thickness effects on WV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
512
5
20

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 799 publications
(561 citation statements)
references
References 8 publications
24
512
5
20
Order By: Relevance
“…The downstream resistance of air (Schwartzberg, 1986) was minimized by operating a fan inside the chamber to provide an airflow of 259 m/ min over the cups. McHugh et al (1993) observed an increase in water vapor permeability of hydrophilic films with an increase in air flow rate up to 152 m/min, after which the increase was negligible. The rate of weight loss, which was constant at steady state, was used to calculate P. When Henry's law is obeyed, the loss rate or WVTR is (Rogers, 1985):…”
Section: Determination Of Water Vapor Permeabilitymentioning
confidence: 89%
See 1 more Smart Citation
“…The downstream resistance of air (Schwartzberg, 1986) was minimized by operating a fan inside the chamber to provide an airflow of 259 m/ min over the cups. McHugh et al (1993) observed an increase in water vapor permeability of hydrophilic films with an increase in air flow rate up to 152 m/min, after which the increase was negligible. The rate of weight loss, which was constant at steady state, was used to calculate P. When Henry's law is obeyed, the loss rate or WVTR is (Rogers, 1985):…”
Section: Determination Of Water Vapor Permeabilitymentioning
confidence: 89%
“…The slightly greater P eff reported by Gennadios et al (1993) was probably due to the thicker films (≈100 μm) used in that study. Generally, P eff of hydrophilic films increases with film thickness, as shown for protein films from sodium caseinate (McHugh et al, 1993) and soy protein isolate (Ghorpade et al, 1995).…”
Section: Effective Water Vapor Permeabilitymentioning
confidence: 99%
“…WVP is also a measure wherein moisture can pass through a material very easily. Gelatin films, which are usually hydrophilic in nature, exhibit a positive slope relationship between thickness and WVP that results from variations in the water vapor (partial) pressure at the underside of the film during testing (McHugh et al 1993). Hence, it is necessary to compare film thickness with WVP values.…”
Section: Water Vapor Permeabilitymentioning
confidence: 99%
“…The cups were placed in desiccators with distilled water at 30°C. The cups were weighed at intervals of 1 h over a 12 h period and WVP (g·m -1 · s -1 ·Pa -1 ) of the film was calculated as follows: WVP=(w· x)/A · t · (P2-P1) [10], where w is the weight gain of the cup (g), x is the film thickness (mm), A is the area of exposed films (m 2 ), t is the time of gain (s), and (P2-P1) is the vapor pressure differential across the film (Pa).…”
Section: Measurements Of Water Vapour Permeability (Wvp)mentioning
confidence: 99%